A method for preparing a carbon-containing lithium sulfide composite material
Lithium sulfide is prepared by ball milling in a vacuum glove box, and dissolved and filtered in anhydrous ethanol and added to a carbon source for treatment, which solves the problems of low purity, high cost and poor environmental protection in the prior art, and achieves high purity, low cost and environmentally friendly lithium sulfide preparation.
Patent Information
- Application Number
- CN202411752621.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
AI Technical Summary
The existing lithium sulfide preparation methods have problems with low purity, high cost and environmental protection, and cannot take into account both high purity, low cost and environmental protection.
In a vacuum glove box, the lithium source and sulfur source are mixed with sodium borohydride by ball milling to obtain crude lithium sulfide, which is dissolved and filtered in anhydrous ethanol, added with carbon source and stirred and sonicated, and finally obtained a high-purity Li2S/C composite material by freeze-drying.
The purity of lithium sulfide is improved, production costs are reduced, harmful gases are avoided, and the introduction of carbon materials is improved to improve electrical conductivity and cycle performance.
Smart Images

Figure CN119750502A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium sulfide preparation, and in particular to a method for preparing a carbon-containing lithium sulfide composite material. Background Art
[0002] At present, lithium-ion batteries have been widely used in electric vehicles, aerospace, energy storage devices, electronic products and other fields. However, limited by the choice of positive electrode active materials, the specific energy (energy stored per unit mass or volume) of traditional commercial lithium-ion batteries has approached the theoretical limit and cannot meet the development needs of the next generation of battery energy storage industry. As one of the key raw materials for the production of solid-state batteries and lithium-sulfur batteries, lithium sulfide has a good prospect for use in solid-state batteries due to its high conductivity, good thermal stability, and theoretical specific capacity of up to 1166mA·h / g.
[0003] Common lithium sulfide preparation methods include ball milling, carbon thermal reduction, solvent thermal and high temperature / high pressure. Among them, the ball milling method is to mix sulfur and metallic lithium in proportion, and then perform simple mechanical ball milling under the protection of inert gas to obtain lithium sulfide positive electrode material. However, the lithium sulfide obtained by this method is impure, and the reaction raw material metallic lithium is expensive, the production cost is relatively high, and it is not conducive to industrial production. The carbon thermal reduction method uses the reducing property of carbon to directly reduce lithium sulfate compounds to lithium sulfide. This process will produce greenhouse gases and CO, which is not in line with the low-carbon and environmentally friendly production concept.
[0004] The solvothermal method is to dissolve lithium salt in an organic solvent and heat it to a certain temperature, then introduce hydrogen sulfide gas to react and prepare lithium sulfide, such as patent CN 105016310 A. The advantage of this method is that it is easy to purify and recover the solvent, minimizing waste, but it has disadvantages such as organic solvents are flammable and explosive, and hydrogen sulfide gas is highly toxic and environmentally unfriendly.
[0005] The principle of the high temperature / high pressure method is that lithium or lithium compounds and sulfur compounds are reduced or reacted in the gas phase under high temperature and high pressure under inert gas / reducing protective gas, such as patent CN 102177090 A. The lithium sulfide obtained by this method has high purity, no harmful gas is generated, and it is environmentally friendly. However, due to the high temperature and high pressure reaction conditions, the energy consumption is high.
[0006] In summary, the existing methods for preparing lithium sulfide have certain defects and cannot take into account purity, low cost and environmental protection at the same time. Summary of the invention
[0007] In view of this, an object of the present invention is to provide a method for preparing a carbon-containing lithium sulfide composite material, aiming to solve at least one technical problem in the prior art raised by the background technology.
[0008] An object of the present invention is to provide a method for preparing a carbon-containing lithium sulfide composite material, the method comprising:
[0009] In a water-free and oxygen-free environment of a vacuum glove box, a certain amount of lithium source and sulfur source are weighed and placed in a ball mill, and then sodium borohydride is added according to a set ratio and mixed evenly;
[0010] The ball mill is sealed, and an inert gas is introduced after vacuuming, and then the ball mill is performed at a set speed for a certain period of time. After the ball milling is completed, the lithium sulfide solid is taken out under the protection of the inert gas;
[0011] The obtained lithium sulfide solid was dissolved in anhydrous ethanol, filtered, and a certain amount of carbon source was added to the filtrate, stirred, and ultrasonically treated; then heated and evaporated to remove the solvent to obtain solid Li 2 S / C precursor;
[0012] Li 2 The S / C precursor was placed in a vacuum freeze dryer and freeze-dried to remove residual water to obtain Li 2 S / C composite material.
[0013] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the sulfur source is sulfur, and the lithium source is anhydrous lithium hydroxide or lithium hydroxide monohydrate.
[0014] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the stoichiometric ratio of the lithium source, the sulfur source and the sodium borohydride is 1.5-2:1:2-3.
[0015] Furthermore, in the method for preparing the above-mentioned carbon-containing lithium sulfide composite material, the inert gas is any one of nitrogen, argon and helium, the ball milling speed is 100r / min to 500r / min, and the ball milling time is 1h to 36h.
[0016] Furthermore, in the method for preparing the above-mentioned carbon-containing lithium sulfide composite material, the carbon source is one or more of cellulose nanocrystals, carbon nanotubes, carbon ink, sodium alginate and MXene.
[0017] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the amount of carbon source added is 20% to 30%.
[0018] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the stirring speed is 300 r / min to 400 r / min, and the stirring time is 1 to 6 hours.
[0019] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the power of the ultrasonic treatment is 500 W, and the ultrasonic time is 1 h to 2 h.
[0020] Furthermore, in the method for preparing the carbon-containing lithium sulfide composite material, the freeze-drying temperature is -40 to -60°C.
[0021] Another object of the present invention is to provide a carbon-containing lithium sulfide composite material, which is prepared by the above-mentioned method for preparing the carbon-containing lithium sulfide composite material.
[0022] Compared with the prior art: the embodiment of the present invention puts the lithium source and the sulfur source into a ball mill, then adds sodium borohydride and mixes evenly to obtain a crude lithium sulfide product, and dissolves the crude lithium sulfide product obtained by the ball milling method in ethanol. By utilizing the solubility of lithium sulfide in ethanol, the insoluble raw materials and other impurities can be filtered to obtain lithium sulfide with low impurity content and high product purity, thereby improving the problem of high impurity content of the product obtained by the ball milling method; hydrogen sulfide gas is not involved, thus avoiding the problem of environmental unfriendliness of the solvent thermal method, and compared with the high temperature / high pressure method, the energy consumption is low and safe; and the introduction of carbon materials can not only solve the problems of poor conductivity and "shuttle effect" of lithium sulfide, but also improve the battery cycle and coulomb efficiency. The problem of high cost and low purity in the preparation of lithium sulfide in the prior art is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is a flow chart of a method for preparing a carbon-containing lithium sulfide composite material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] In addition, the term "and / or" as used herein includes any and all combinations of one or more related listed items. In the detailed description and claims, a list of items connected by the term "one of" may mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements. In the detailed description and claims, a list of items connected by the terms "at least one of", "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" or "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" or "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0027] The present invention aims to solve the problem of high cost and low purity in the current preparation of lithium sulfide, and proposes a method for preparing a carbon-containing lithium sulfide composite material. Figure 1 , wherein the method comprises:
[0028] Step S10, in a water-free and oxygen-free environment of a vacuum glove box, weigh a certain amount of lithium source and sulfur source, put them into a ball mill, and then add sodium borohydride according to a set ratio and mix them evenly.
[0029] The sulfur source is sulfur, and the lithium source is anhydrous lithium hydroxide or monohydrate lithium hydroxide. Compared with lithium metal, the price of anhydrous lithium hydroxide or monohydrate lithium hydroxide is relatively cheap, which can greatly reduce the industrial production cost. Specifically, the raw materials lithium source, sulfur source and sodium borohydride are in a certain stoichiometric ratio of 1.5-2:1:2-3.
[0030] Step 11, sealing the ball mill jar, introducing an inert gas after evacuation, and then ball milling for a certain period of time at a set speed. After the ball milling is completed, the lithium sulfide solid is taken out under the protection of the inert gas.
[0031] The inert gas is one of nitrogen, argon and helium. The ball milling speed is set to 100-500 r / min, and the ball milling time is set to 1-36 h.
[0032] Step S12, dissolving the obtained lithium sulfide solid in anhydrous ethanol, filtering, adding a certain amount of carbon source to the filtrate, stirring, and ultrasonically treating; then heating and evaporating to remove the solvent to obtain a solid Li2S / C precursor.
[0033] Among them, the crude lithium sulfide obtained by ball milling is dissolved in ethanol, and the solubility of lithium sulfide in ethanol can be used to filter insoluble raw materials and other impurities to obtain lithium sulfide with low impurity content and high product purity. To improve the problem of high impurity content of the product obtained by ball milling, specifically, the carbon source is one or more of cellulose nanocrystals, carbon nanotubes, carbon ink, sodium alginate and MXene, the amount of carbon source added is 20% to 30%, the stirring speed is 300r / min to 400r / min, the stirring time is 1 to 6 hours, the power of ultrasonic treatment is 500W, the ultrasonic time is 1h to 2h, and further purification and composite conductive carbon material modification are carried out through the recrystallization process. After the recrystallization is completed, the solvent is removed by heating and evaporation to leave a solid Li2S / C precursor.
[0034] Step S13: Li 2 The S / C precursor was placed in a vacuum freeze dryer and freeze-dried to remove residual water to obtain Li 2 S / C composite material.
[0035] The solid obtained by evaporation is placed in a vacuum freeze dryer for freeze drying to remove residual moisture, and finally a high-purity Li2S / C composite material is obtained. Specifically, the vacuum freeze drying temperature is -40 to -60°C.
[0036] Another aspect of the present invention further provides a carbon-containing lithium sulfide composite material, which is prepared by the above-mentioned method for preparing the carbon-containing lithium sulfide composite material.
[0037] In order to facilitate understanding of the present invention, several embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0038] Example 1
[0039] In the anhydrous and oxygen-free environment of a vacuum glove box, 14.5 g of lithium hydroxide and 10 g of sulfur were weighed in a stoichiometric ratio of 2:1:2, respectively, and placed in a ball mill, and then 23 g of sodium borohydride was added and mixed evenly. The ball mill was sealed, and argon was introduced after vacuuming, and then ball milled at a speed of 300 r / min for 24 hours. After the ball milling was completed, the crude solid of lithium sulfide was taken out under the protection of argon. Then, the obtained crude solid of lithium sulfide was dissolved in anhydrous ethanol, filtered, and 20% of cellulose nanocrystals of the mass of lithium sulfide were added to the filtrate. Stir at a speed of 300 r / min for 4 hours at room temperature, and ultrasonically treated at 500W for 1 hour to further purify and modify the composite conductive carbon material. The solvent was removed by heating and evaporation, leaving a solid Li2S / C precursor composite material. Finally, the evaporated solid was freeze-dried to remove residual moisture to obtain a high-purity Li2S / C composite material.
[0040] Example 2
[0041] In the anhydrous and oxygen-free environment of a vacuum glove box, 13 g of lithium hydroxide and 10 g of sulfur were weighed in a stoichiometric ratio of 1.8:1:2, respectively, and placed in a ball mill, and then 23 g of sodium borohydride was added and mixed evenly. The ball mill was sealed, and argon was introduced after vacuuming, and then ball milled at a speed of 300 r / min for 24 hours. After the ball milling was completed, the crude solid of lithium sulfide was taken out under the protection of argon. Then, the obtained crude solid of lithium sulfide was dissolved in anhydrous ethanol, filtered, and 20% of cellulose nanocrystals of the mass of lithium sulfide were added to the filtrate. Stir at a speed of 300 r / min for 4 hours at room temperature, and ultrasonically treated at 500W for 1 hour to further purify and modify the composite conductive carbon material. The solvent was removed by heating and evaporation, leaving a solid Li2S / C precursor composite material. Finally, the evaporated solid was freeze-dried to remove residual moisture to obtain a high-purity Li2S / C composite material.
[0042] Example 3
[0043] In the anhydrous and oxygen-free environment of a vacuum glove box, 12 g of lithium hydroxide and 10 g of sulfur were weighed in a stoichiometric ratio of 1.6:1:2, respectively, and placed in a ball mill, and then 23 g of sodium borohydride was added and mixed evenly. The ball mill was sealed, and argon was introduced after vacuuming, and then ball milled at a speed of 300 r / min for 24 hours. After the ball milling was completed, the crude solid of lithium sulfide was taken out under the protection of argon. Then, the obtained crude solid of lithium sulfide was dissolved in anhydrous ethanol, filtered, and 20% of the mass of lithium sulfide sodium alginate was added to the filtrate. Stir at a speed of 300 r / min for 4 hours at room temperature, and ultrasonically applied at 500W for 1 hour to further purify and modify the composite conductive carbon material. The solvent was removed by heating and evaporation, leaving a solid Li2S / C precursor composite material. Finally, the evaporated solid was freeze-dried to remove residual moisture to obtain a high-purity Li2S / C composite material.
[0044] Example 4
[0045] In the anhydrous and oxygen-free environment of a vacuum glove box, 13g of lithium hydroxide and 10g of sulfur were weighed in a stoichiometric ratio of 1.8:1:3, respectively, and placed in a ball mill, and then 35g of sodium borohydride was added and mixed evenly. The ball mill was sealed, and argon was introduced after vacuuming, and then ball milled at a speed of 300r / min for 24 hours. After the ball milling was completed, the crude solid of lithium sulfide was taken out under the protection of argon. Then, the obtained crude solid of lithium sulfide was dissolved in anhydrous ethanol, filtered, and 20% of the mass of sodium alginate of lithium sulfide was added to the filtrate. Stir at a speed of 300r / min for 4 hours at room temperature, and ultrasonically treated at 500W for 1 hour to further purify and modify the composite conductive carbon material. The solvent was removed by heating and evaporation, leaving a solid Li2S / C precursor composite material. Finally, the evaporated solid was freeze-dried to remove residual moisture to obtain a high-purity Li2S / C composite material.
[0046] Comparative Example 1
[0047] In the anhydrous and oxygen-free environment of a vacuum glove box, 14.5g of lithium hydroxide and 10g of sulfur were weighed in a stoichiometric ratio of 2:1:2, respectively, and placed in a ball mill, and then 23g of sodium borohydride was added and mixed evenly. The ball mill was sealed, and argon was introduced after vacuuming, and then ball milled at a speed of 300r / min for 24 hours. After the ball milling was completed, the crude solid of lithium sulfide was taken out under the protection of argon. Then, the obtained crude solid of lithium sulfide was mixed with 20% cellulose nanocrystals and ultrasonicated at 500W for 1 hour in anhydrous ethanol solvent at room temperature. The solvent was removed by heating and evaporation, leaving a solid Li2S / C precursor composite material. Finally, the evaporated solid was freeze-dried to remove residual moisture to obtain a high-purity Li2S / C composite material. The 0.1C first discharge capacity of this composite material is 865.3mA h / g, and the discharge capacity is only 580.3mA h / g after 200 cycles.
[0048] Comparative Example 2
[0049] The method for preparing lithium sulfide and its carbon composite material based on lithium hydroxide provided in this comparative example is basically the same as that in Example 3, the difference is that the crude lithium sulfide is not recrystallized or filtered with anhydrous ethanol, but is directly subjected to ultrasound using anhydrous ethanol as a solvent.
[0050] Please refer to the following Table 1, which shows the performance parameters of the lithium sulfide prepared in the above Examples 1-4 and Comparative Examples 1-2 of the present invention.
[0051] Table 1
[0052]
[0053] In addition, it can be clearly seen from Example 1 and the comparative example that the discharge specific capacity of the unpurified Li2S / C composite material is significantly lower than that of the purified composite material. Since the unpurified lithium sulfide may contain other impurities and unreacted lithium hydroxide, the proportion of lithium sulfide is low, which affects the specific capacity.
[0054] It can be clearly seen from Examples 1 and 2 that the appropriate ratio allows the lithium source to fully react to form lithium sulfide, reduces the generation of polysulfides, and improves the purity of lithium sulfide;
[0055] It can be clearly seen from Examples 1 to 4 that when the ratio of lithium source, sulfur source, and sodium borohydride is 1.8:1:2, the discharge capacity of purified and used cellulose nanocrystals is the best; therefore, reasonable purification treatment and ratio as well as the selection of carbon source help the lithium source to fully react to form lithium sulfide, reducing the formation of polysulfides, which can cause the shuttle effect. Furthermore, the lithium-sulfur ratio is controlled and the purity of lithium sulfide is increased to improve the discharge efficiency.
[0056] In summary, the embodiment of the present invention is to put the lithium source and the sulfur source into a ball mill, then add sodium borohydride and mix evenly to obtain a crude lithium sulfide product, and dissolve the crude lithium sulfide product obtained by the ball milling method in ethanol. By utilizing the solubility of lithium sulfide in ethanol, the insoluble raw materials and other impurities can be filtered to obtain lithium sulfide with low impurity content and high product purity, thereby improving the problem of high impurity content of the product obtained by the ball milling method; hydrogen sulfide gas is not involved, thus avoiding the problem of the solvent thermal method being unfriendly to the environment, and compared with the high temperature / high pressure method, the energy consumption is low and safe; and the introduction of carbon materials can not only solve the problems of poor conductivity and "shuttle effect" of lithium sulfide, but also improve the battery cycle and coulomb efficiency. The problem of high cost and low purity in the preparation of lithium sulfide in the prior art is solved.
[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a carbon-containing lithium sulfide composite material, characterized in that: The method comprises: In a water-free and oxygen-free environment of a vacuum glove box, a certain amount of lithium source and sulfur source are weighed and placed in a ball mill, and then sodium borohydride is added according to a set ratio and mixed evenly; The ball mill is sealed, and an inert gas is introduced after vacuuming, and then the ball mill is performed at a set speed for a certain period of time. After the ball milling is completed, the lithium sulfide solid is taken out under the protection of the inert gas; The obtained lithium sulfide solid is dissolved in anhydrous ethanol, filtered, and a certain amount of carbon source is added to the filtrate, followed by stirring and ultrasonic treatment; the solvent is then evaporated by heating to obtain a solid Li2S / C precursor; The Li2S / C precursor was placed in a vacuum freeze dryer and freeze-dried to remove residual moisture to obtain a Li2S / C composite material.
2. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The sulfur source is sulfur, and the lithium source is anhydrous lithium hydroxide or monohydrate lithium hydroxide.
3. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The stoichiometric ratio of the lithium source, the sulfur source and the sodium borohydride is 1.5-2:1:2-3.
4. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The inert gas is any one of nitrogen, argon and helium, the rotation speed of the ball mill is 100 r / min to 500 r / min, and the ball milling time is 1 h to 36 h.
5. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The carbon source is one or more of cellulose nanocrystals, carbon nanotubes, carbon ink, sodium alginate and MXene.
6. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The amount of carbon source added is 20% to 30%.
7. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The stirring speed is 300 r / min to 400 r / min, and the stirring time is 1 to 6 hours.
8. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The power of ultrasonic treatment is 500W, and the ultrasonic time is 1h to 2h.
9. The method for preparing the carbon-containing lithium sulfide composite material according to claim 1, characterized in that: The freeze-drying temperature is -40 to -60°C.
10. A carbon-containing lithium sulfide composite material, characterized in that: The carbon-containing lithium sulfide composite material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation of lithium sulfide
CN102177090A
Preparation method and device of high-purity lithium sulfide
CN105016310A
Cited By
All-solid-state lithium-sulfur battery three-dimensional elastic conductive positive electrode frame structure material and preparation method thereof
CN120300190A
A three-dimensional elastic conductive positive electrode frame structure material for all-solid-state lithium-sulfur batteries and its preparation method
CN120300190B
Carbon-coated nano lithium sulfide-C3N4 composite material as well as preparation method and application thereof
CN121076104A